Gagea deyuanana (Liliaceae), a new species of Gagea (Liliaceae) from Xinjiang, north-western China - Qiu, Juan; Zhang, Jun; Lin, Musen; Tan, Dunyan (Phytotaxa, 2026)
A new species, Gagea deyuanana (Liliaceae) is described and illustrated from Xinjiang, China. This new species is like G. filiformis and G. granulosa in the G. section Minimae, but is clearly distinguished by its narrowly ovoid, greyish brown and membranous bulbs, two basal leaves, reticulate cristate pollen exine ornamentation and pentaploid cytotype. Based on the assessment conducted according to the IUCN Red List criteria, we propose that Gagea deyuanana be classified as endangered (EN) species.